2021
DOI: 10.1038/s41598-021-97820-4
|View full text |Cite
|
Sign up to set email alerts
|

Robust neuronal differentiation of human iPSC-derived neural progenitor cells cultured on densely-spaced spiky silicon nanowire arrays

Abstract: Nanostructured cell culture substrates featuring nanowire (NW) arrays have been applied to a variety of basic cell lines and rodent neurons to investigate cellular behavior or to stimulate cell responses. However, patient-derived human neurons—a prerequisite for studying e.g. neurodegenerative diseases efficiently—are rarely employed due to sensitive cell culture protocols and usually long culturing periods. Here, we present human patient induced pluripotent stem cell-derived neurons cultured on densely-spaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Other glass surface modifications for neuron cultures have focused on neurite outgrowth ( Cesca et al., 2014 ; Corey et al., 1991 ; Li et al., 2015 ; Liu et al., 2006 ) or neural stem cell differentiation ( Ananthanarayanan et al., 2010 ; Chen et al., 2018b ), but not sustained neuronal adhesion. Recently nano-structured glass was shown to facilitate PSC-derived neuron functionality ( Harberts et al., 2021 ), but again, cultures were not tested >20 days. An additional benefit of plasma polymer treatment is that the refractive index (and hence, magnitude of attractive van der Waals interactions) can be tailored to further promote the adhesion of various cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Other glass surface modifications for neuron cultures have focused on neurite outgrowth ( Cesca et al., 2014 ; Corey et al., 1991 ; Li et al., 2015 ; Liu et al., 2006 ) or neural stem cell differentiation ( Ananthanarayanan et al., 2010 ; Chen et al., 2018b ), but not sustained neuronal adhesion. Recently nano-structured glass was shown to facilitate PSC-derived neuron functionality ( Harberts et al., 2021 ), but again, cultures were not tested >20 days. An additional benefit of plasma polymer treatment is that the refractive index (and hence, magnitude of attractive van der Waals interactions) can be tailored to further promote the adhesion of various cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Dead cells were sorted out in the pipeline by discrimination of bright nuclei (apoptotic) and medium bright nuclei (viable). [ 48 ] Viable cells were used to mask the MAP2 channel to identify MAP2‐positive cells. The NeuN/TH channels were masked by the MAP2‐positive cells to identify NeuN/TH‐positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we showed the general feasibility of generating human iPSC-derived neurons on NW arrays, but the utilized substrates featured only about 1 µm long NWs. [47,48] As a result, their rather basic topographies just induced a limited amount of deformational stress toward the cells. The impact of other NW array geometries-for instance, with longer NWs-on the neuronal differentiation is still unclear and thus has been addressed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Low rates of reproducibility and efficiency for some existing differentiation protocols may also hinder cell-type specific analyses and integration of data across different research groups. Several adaptations have emerged to overcome potential challenges of 2D models and develop more physiologically relevant networks and substrates, such as nanowire arrays ( 186 , 187 ), sandwich cultures ( 188 ), micropatterning of cell-adhesive islands ( 189 ), modulated substrates ( 190 ), and microfluidic devices ( 191 ). Few, however, have been applied to study iPSC-based models of neurotropic viruses.…”
Section: Two-dimensional Culturesmentioning
confidence: 99%